Immunobiology of Gestational Diabetes Mellitus in Post-Medawar Era - Sharma, Surendra; Banerjee, Sayani; Krueger, Paula M.; Blois, Sandra M. (Frontiers in Immunology, 2022)
Although the concepts related to fetal immune tolerance proposed by Sir Peter Medawar in the 1950s have not withstood the test of time, they revolutionized our current understanding of the immunity at the maternal-fetal interface. An important extension of the original Medawar paradigm is the investigation into the underlying mechanisms for adverse pregnancy outcomes, including recurrent spontaneous abortion, preterm birth, preeclampsia and gestational diabetes mellitus (GDM). Although a common pregnancy complication with systemic symptoms, GDM still lacks understanding of immunological perturbations associated with the pathological processes, particularly at the maternal-fetal interface. GDM has been characterized by low grade systemic inflammation that exacerbates maternal immune responses. In this regard, GDM may also entail mild autoimmune pathology by dysregulating circulating and uterine regulatory T cells (Tregs). The aim of this review article is to focus on maternal-fetal immunological tolerance phenomenon and discuss how local or systemic inflammation has been programmed in GDM. Specifically, this review addresses the following questions: Does the inflammatory or exhausted Treg population affecting the Th17:Treg ratio lead to the propensity of a pro-inflammatory environment? Do glycans and glycan-binding proteins (mainly galectins) contribute to the biology of immune responses in GDM? Our understanding of these important questions is still elementary as there are no well-defined animal models that mimic all the features of GDM or can be used to better understand the mechanistic underpinnings associated with this common pregnancy complication. In this review, we will leverage our preliminary studies and the literature to provide a conceptualized discussion on the immunobiology of GDM.